2016
DOI: 10.1038/ncomms12638
|View full text |Cite
|
Sign up to set email alerts
|

RNF168 and USP10 regulate topoisomerase IIα function via opposing effects on its ubiquitylation

Abstract: Topoisomerase IIα (TOP2α) is essential for chromosomal condensation and segregation, as well as genomic integrity. Here we report that RNF168, an E3 ligase mutated in the human RIDDLE syndrome, interacts with TOP2α and mediates its ubiquitylation. RNF168 deficiency impairs decatenation activity of TOP2α and promotes mitotic abnormalities and defective chromosomal segregation. Our data also indicate that RNF168 deficiency, including in human breast cancer cell lines, confers resistance to the anti-cancer drug a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 60 publications
1
23
0
Order By: Relevance
“…Introduction or removal of ubiquitin is also a mechanism of drug resistance, as it modulates the Top2a activities and protein levels through proteasome degradation [53][54][55] . Deficiency in the RNF168 E3 ubiquitin ligase in breast cancer cells, or elevated levels of ubiquitin ligase Mdm2 in osteosarcoma cells, confers resistance to the Top2 poison etoposide, by regulating Top2 activities [53,56] . Ubiquitin-mediated degradation of Top2 also contributes to the level of drug resistance in solid tumors since proteasome inhibition leads to etoposide resistance [57] .…”
Section: Ubiquitinations and Sumoylationsmentioning
confidence: 99%
“…Introduction or removal of ubiquitin is also a mechanism of drug resistance, as it modulates the Top2a activities and protein levels through proteasome degradation [53][54][55] . Deficiency in the RNF168 E3 ubiquitin ligase in breast cancer cells, or elevated levels of ubiquitin ligase Mdm2 in osteosarcoma cells, confers resistance to the Top2 poison etoposide, by regulating Top2 activities [53,56] . Ubiquitin-mediated degradation of Top2 also contributes to the level of drug resistance in solid tumors since proteasome inhibition leads to etoposide resistance [57] .…”
Section: Ubiquitinations and Sumoylationsmentioning
confidence: 99%
“…UBE1, Ubc13, and Ub recombinant proteins were gifts from C. Arrowsmith (Princess Margaret Cancer Centre, University Health Network and Department of Medical Biophysics, University of Toronto, Toronto, Ontario, Canada). Recombinant N1ICD (2 μg; Addgene, 47612), recombinant RNF8 (1 μg), UBE1 (0.1 μg; E1), Ubc13 (0.2 μg; E2), Ub (5 μg), and ATP (5 mM) were mixed, and the reactions were incubated at 30°C for 2 hours in buffer containing 50 mM Tris/HCl (pH 7.5), 5 mM MgCl 2 , and 1 mM DTT and examined by immunoblot as previously reported (39).…”
Section: Methodsmentioning
confidence: 99%
“…Several lines of evidence have unraveled the diverse roles of USP10 in tumorigenesis as well as malignancy in different cancer types (Guturi et al, 2016;Lin et al, 2013;Sun et al, 2018;Weisberg et al, 2017;Yang et al, 2014;Yuan et al, 2010). Lin et al found that USP10 antagonizes the transcriptional activity of c-Myc by deubiquitinating and stabilizing SIRT6, to inhibit cell growth and tumor formation in colon cancers (Lin et al, 2013).…”
Section: Discussionmentioning
confidence: 99%